Emerging functions of the wellbeing concept in regional development scholarship: A review. Issue 115 (January 2021) - Fudge, Maree; Ogier, Emily; Alexander, Karen A.
Highlights: Wellbeing 'turn' influencing regional development. The concepts are differently constituted. Nuanced and mixed methods approach is required. Abstract: Wellbeing has become important in regional development policy as decision-makers grapple with delivering public goods from industry exploitation of resource commons. We asked how these differently constituted concepts–'regional development' and 'wellbeing' – are handled in the literature. We identified four findings: i) an increasing focus on holistic sustainable development in regional development; ii) different approaches for pre-development planning and post-development impact assessment; iii) four key wellbeing components most common in regional development; iv) emergence of mixed methods approaches to investigating wellbeing and regional development. We conclude that synthesising wellbeing and regional development within a carefully designed interdisciplinary approach is required.